Latent dimensions of museum experience: assessing cross-cultural perspectives of visitors from tripadvisor reviews. (2nd November 2022) - Riva, Paola; Agostino, Deborah
ABSTRACT: Museums must assess visitors' experience to understand them and their needs. TripAdvisor provides an accessible source of user-generated data about the visit experience, but there is limited empirical evidence on the value of automated elaboration of this data for museum management. This paper uses topic modeling to identify the latent dimensions of the visit experience for the 30 most-visited Italian museums in 2019 using online reviews. Differences in the latent dimensions are assessed between visitors with different cultural backgrounds, as identified by whether they write in the local or non-local language. The results show that while all visitors share three cross-cultural dimensions of experience (museum cultural heritage, personal experience, and museum services), specific latent dimensions are emphasized by local (i.e., 'wow effect' and hospitality) and non-local visitors (i.e., time management and unfavorable experiences).